Gut reactions a perceptual theory of emotion - Prinz, Jesse J. (Philosophy of mind series, 2004)
"Gut Reactions is an interdisciplinary defense of the claim that emotions are perceptions of changes in the body. This thesis, pioneered by William James and resuscitated by Antonio Damasio, has been widely criticized for failing to acknowledge that emotions are meaningful insofar as they represent concerns, not respiratory function and blood pressure. Fear represents danger, sadness represents loss. To explain this fact, many researchers conclude that emotions must involve judgments regarding one's relationship to the environment. Prinz offers a new unified account of the emotions that reconciles these two theories. He argues that emotions are embodied appraisals - they are perceptions of the body, but, through the body, they also allow us to literally perceive danger, loss, and other matters of concern."--BOOK JACKET.